Construction of mathematical model of wear with the specified parameters - Артемчук, В.В. (Problems of Tribology, 2014)
The design of wear of details, having curvilinear surfaces is considered in the article. The mathematical model of wear, the parameters of the attended bodies and contact tensions, arising up in the spot of contact are taken into account in which, is offered. The method of calculation of parameters of area of contact and parameters of deformation is offered with the use of the special integral.